Workplace Assessment of Security Guards in Selected Establishments in Manila - Bautista, Maureen L.; Esmilla, Rodel G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
ABSTRACT This study was conducted to assess the workplace of security guards in selected establishments in Manila. Specifically, this looked into the: 1) demographic profile of the security guards in terms of age, sex, civil status, educational attainment, and years of experience; 2) workplace assessment of security guards in terms of organizational factor, individual factor, and work environment factor; and 3) significant relationship between the security guards’ workplace assessment and demographic profile. Descriptive research method was utilized in this study. Self-made survey questionnaire was administered to the security guards who voluntarily participated in this study and who were assigned in three establishments which were composed of a transportation establishment, a university, and a mall. Stratified random sampling technique was employed in selecting the security guards. The study revealed that the security guards had an average assessment of their workplace in terms of organizational, individual and work environment factor. Based on the findings, with reference to the security guards’ demographic profile, it was concluded that the security guards’ nature of work such as being risky and dangerous demands physical agility and that age and sex are a primary consideration. On years of experience, most of the security guards had less than six months of experience. With regard workplace factors as organizational, individual, and work environment; these simultaneously impacted security guards’ assessment of their workplace. Likewise, it was noted that all these three factors directly affected their well-being and work performance. Likewise, significant relationship between security guards’ profile and their assessment of workplace was noted in the following: age and organizational factor which may suggest that age influences career growth; educational attainment, organizational factor, and work environment factor which may indicate that educational biography impacts career advancement which determines one’s job role and consequently affects one’s work environment; and years of experience and organizational factor which may embody job experience and employee loyalty in the company which impact career progression. Based on the conclusions, this study generally recommends to have continuous conduct of employee orientation to encourage employee engagement and performance of functions in accordance with company context, provision of security-related equipment, continuous training to enhance capability in performing their roles and career advancement, and formulation of program to address negative effects of demanding role of security guards to well-being.